Yi-Qi-Jian-Pi Formula Suppresses RIPK1/RIPK3-Complex-Dependent Necroptosis of Hepatocytes Through ROS Signaling and Attenuates Liver Injury in Vivo and in Vitro - Wang, Feixia; Tang, Li; Liang, Baoyu; Jin, Chun; Gao, Liyuan; Li, Yujia; Li, Zhanghao; Shao, Jiangjuan; Zhang, Zili; Tan, Shanzhong; Zhang, Feng; Zheng, Shizhong (Frontiers in Pharmacology, 2021)
Acute-on-chronic liver failure (ACLF) is described as a characteristic of acute jaundice and coagulation dysfunction. Effective treatments for ACLF are unavailable and hence are urgently required. We aimed to define the effect of Yi-Qi-Jian-Pi Formula (YQJPF) on liver injury and further examine the molecular mechanisms. In this study, we established CCl4-, LPS-, and D-galactosamine (D-Gal)-induced ACLF rat models in vivo and LPS- and D-Gal-induced hepatocyte injury models in vitro. We found that YQJPF significantly ameliorates liver injury in vivo and in vitro that is associated with the regulation of hepatocyte necroptosis. Specifically, YQJPF decreased expression of receptor-interacting protein kinase 1 (RIPK1), receptor-interacting protein kinase 3 (RIPK3) and pseudokinase mixed lineage kinase domain-like (MLKL) to inhibit the migration of RIPK1 and RIPK3 into necrosome. YQJPF also reduces the expression of inflammatory cytokines IL-6, IL-8, IL-1β, and TNF-α, which were regulated by RIPK3 mediates cell death. RIPK1 depletion was found to enhance the protective effect of YQJPF. Furthermore, we showed that YQJPF significantly downregulates the mitochondrial reactive oxygen species (ROS) production and mitochondrial depolarisation, with ROS scavenger, 4-hydroxy-TEMPO treatment recovering impaired RIPK1-mediated necroptosis and reducing the expression of IL-6, IL-8, IL-1β, and TNF-α. In summary, our study revealed the molecular mechanism of protective effect of YQJPF on hepatocyte necroptosis, targeting RIPK1/RIPK3-complex-dependent necroptosis via ROS signalling. Overall, our results provided a novel perspective to indicate the positive role of YQJPF in ACLF.